Running Pure : The Importance of Forest Protected Areas to Drinking Water - Dudley, Nigel (World Bank/WWF Alliance for Forest Conservation and Sustainable Use, 2013)
This report focuses on one specific interaction: the role of forests, and particularly protected forests, in maintaining quality of drinking water for large cities. There are many reasons for this focus: many city dwellers already face a crisis of water quality, and contaminated water spreads a vast and largely unnecessary burden in terms of short and long-term health impacts including infant mortality, with knock-on effects on ability to work, industrial productivity and on already over-stretched health services. The poorest members of society, unable to afford sterilized or bottled water, suffer the greatest impacts. Similar problems affect the rural poor as well of course, and sometimes these can be even more severe. However, in a rapidly urbanizing world the scale of the problem facing cities is particularly acute.